2020
DOI: 10.1080/03007995.2020.1747998
|View full text |Cite
|
Sign up to set email alerts
|

The importance of considering differences in study and patient characteristics before undertaking indirect treatment comparisons: a case study of siponimod for secondary progressive multiple sclerosis

Abstract: Adlard (2020) The importance of considering differences in study and patient characteristics before undertaking indirect treatment comparisons: a case study of siponimod for secondary progressive multiple sclerosis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The importance of conducting a detailed assessment of cross-trial heterogeneity when undertaking ITCs was recently demonstrated by Samjoo et al for trials in SPMS patients 35 . In this case, the feasibility assessment highlighted the appreciable cross-trial heterogeneity that would have caused biased results if traditional ITCs, such as Bucher ITCs or NMA were conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of conducting a detailed assessment of cross-trial heterogeneity when undertaking ITCs was recently demonstrated by Samjoo et al for trials in SPMS patients 35 . In this case, the feasibility assessment highlighted the appreciable cross-trial heterogeneity that would have caused biased results if traditional ITCs, such as Bucher ITCs or NMA were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, population-based ITC methods that accounted for disparities in clinical covariates by leveraging IPD were found to be a more valid approach to examining comparative efficacy. Previous studies in MS and several other therapeutic areas have provided insights into the impact of adjustments on the validity of ITCs [35][36][37][38] . In these examples, the clinical interpretation of the comparative efficacy of interventions was altered when accounting for differences in clinically relevant covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NICE recommendation of siponimod for active SPMS relied on the results of a single clinical trial, known as the EXPAND trial 4 . In common with most trials evaluating DMTs, the EXPAND trial outcomes were difficult to interpret 5 . Patients were recruited from 31 countries for the trial.…”
Section: Evidence Of Efficacymentioning
confidence: 99%
“…4 In common with most trials evaluating DMTs, the EXPAND trial outcomes were difficult to interpret. 5 Patients were recruited from 31 countries for the trial. As the definitions of the different subtypes and stages of MS can differ from one country to the other, NICE had to examine the equivalence of the trial's subjects to establ i s h i f t h e c o n c l u s i o n s a n d s u b s e q u e n t recommendations could apply to UK standard practice.…”
mentioning
confidence: 99%